Statistical Analysis of Threshold Algorithms in Image Processing Based Cancer Cell Detection - Koc, Gamze; Sarioglu, Baykal (IEEE, 2014)
In this paper, an algorithm which is implemented for cancer detection in image processing and the results of the algorithm are mentioned. Researched work has three main steps. In first step, images are passed through significant steps for noise removal; at the second step, various histogram thresholds are calculated and at the last step cancer is detected with respect to calculated thresholds. As a result, the highest success rate is obtained as 81.25 percent while the lowest success rate is 37.5 percent.
22nd IEEE Signal Processing and Communications Applications Conference (SIU) -- APR 23-25, 2014 -- Karadeniz Teknik Univ, Trabzon, TURKEY
Keywords: Cancer Detection; Histogram; Threshold